Comparative Study of Bismuth Ferrite Deposition Method on TiO2 Nanotube and Performance of Hydrogen Evolution in a Photoelectrochemical Dye-Sensitized Solar Cell Tandem System - Yunita, Yunita; Syauqi, Muhammad Iqbal; Gunlazuardi, Jarnuzi (UI Scholars Hub, 2022)
Hydrogen is a renewable and environmentally friendly energy source that can replace fossil fuels by utilizing solar energy through water splitting. The hydrogen production was conducted in this research by using a tandem system of dye-sensitized solar cell–photoelectrochemical cell (DSSC–PEC) and a TiO2 nanotube coated with BiFeO3 (BiFeO3/TNT) as a photoanode in the PEC. The deposition of BiFeO3 on TNT was prepared using the following three methods: successive ionic layer adsorption and reaction (SILAR), ultrasonication-assisted SILAR, and ultrasonic– immersion method by varying the number of deposition cycles in each method. In this study, the optimum cycles for SILAR, ultrasonication-assisted SILAR, and ultrasonic–immersion methods were 15, 5, and 3, respectively. Results show that the BiFeO3 deposited on TNT using the ultrasonic–immersion method with three cycles (BiFeO3/TNT_UI3) demonstrates the best photoelectrochemical activity. The tandem system comprises BiFeO3/TNT_UI3 photoanode and Pt-coated TNT dark cathode PEC cell connected to TNT/N719-based DSSC with an efficiency of 1.27%. The constructed DSSC–PEC system could produce 3.11 × 10−6 mol hydrogen in 6 h with a solar-to-hydrogen (STH) efficiency of 0.0033% in an H-type reactor filled with 0.5 M H2SO4 electrolyte.